Resiliensi perempuan setelah kematian pasangan: Sebuah kajian gender - Indira Elvana Lunggita; Made Diah Lestari (Jurnal Pendidikan Indonesia, 2025)
The death of a partner is portrayed as a painful reality, especially for single mothers in Indonesia. Gender inequality is identified as the root cause of the challenges faced by single mothers, leading to the creation of stigma, stereotypes, and marginalization against them. In this context, single mothers require resilience to confront various challenges and overcome adversity. This research aims to explore the dialogue between gender roles and the resilience of women after the loss of their partners. Through a literature review method, data was gathered from previous studies, resulting in the identification of nine articles that met the search criteria. The review findings indicate that, despite facing obstacles in developing resilience based on societal norms and expectations rooted in a patriarchal culture, single mothers are capable of achieving resilience.